Uncertainty in East Antarctic Firn Thickness Constrained Using a Model Ensemble Approach. Issue 7 (1st April 2021) - Verjans, V.; Leeson, A. A.; McMillan, M.; Stevens, C. M.; van Wessem, J. M.; van de Berg, W. J.; van den Broeke, M. R.; Kittel, C.; Amory, C.; Fettweis, X.; Hansen, N.; Boberg, F.; et al.
Abstract: Mass balance assessments of the East Antarctic ice sheet (EAIS) are highly sensitive to changes in firn thickness, causing substantial disagreement in estimates of its contribution to sea‐level. To better constrain the uncertainty in recent firn thickness changes, we develop an ensemble of 54 model scenarios of firn evolution between 1992 and 2017. Using statistical emulation of firn‐densification models, we quantify the impact of firn compaction formulation, differing climatic forcing, and surface snow density on firn thickness evolution. At basin scales, the ensemble uncertainty in firn thickness change ranges between 0.2 and 1.0 cm yr −1 (15%–300% relative uncertainty), with the choice of climate forcing having the largest influence on the spread. Our results show the regions of the ice sheet where unexplained discrepancies exist between observed elevation changes and an extensive set of modeled firn thickness changes estimates, marking an important step toward more accurately constraining ice sheet mass balance. Plain Language Summary: Firn is the transition stage between snow and ice. The total thickness of the firn layer varies in time and space. In East Antarctica, uncertainty about this variability has a large impact on satellite‐based estimates of ice sheet mass change. We combine statistical surrogates of firn‐densification models with different climate models over the entire East Antarctic ice sheet. Our ensemble of model combinations demonstrates that firn thickness estimates are poorly constrained. Accounting for their respective uncertainties, modeled firn thickness change and satellite measurements of elevation change are consistent over most of East Antarctica. However, we identify several areas of mismatch between model estimates and elevation change observations, which likely indicates that further improvements are required either in models or in measurement techniques. Alternatively, these disagreements can hint at possible imbalances in the flow of ice, below the firn layer. We quantify how much different sources of uncertainty contribute to the total uncertainty in modeled firn thickness change. The amount of snowfall estimated by climate models mostly dominates the uncertainty, but modeled firn compaction rates and uncertainty in surface snow density also have major contributions in certain areas. Key Points: By developing an ensemble of 54 model scenarios, we constrain firn thickness change uncertainty in East Antarctica over 1992–2017 In 9 of 16 basins, modeled firn thickness and altimetry trends agree; elsewhere uncertainty is underestimated or ice flow imbalance exists Model uncertainty reaches 1 cm yr −1 with snowfall, firn compaction and snow density having spatially variable contributions to uncertainty